Improving Awareness of Organic Chemistry in Drug Innovation: A Student-CenteredEducational Intervention - Nita Rusdiana; Dina Pratiwi; La Ode Akbar Rasydy; Bina Lohita Sari (Jurnal Sentra Pengabdian, 2025)
Organic chemistry a branch of chemistry that plays a crucial role and serves as a fundamental foundation in the synthesis and analysis of drug molecules. However, students' knowledge of organic chemistry is still limited, especially its connection to the discovery and development of new drugs in the pharmaceutical world. This study aimed to improve pharmacy students' awareness of the role of organic chemistry in drug innovation. The research was conducted at the Faculty of Pharmacy, Muhammadiyah A.R. Fachruddin University, involving 15 secondsemester diploma Pharmacy students and 29 fourth-semester bachelor degree Pharmacy students. Theresearch approach used in this community service is a Participatory Action Research (PAR) design.The research instrument was a questionnaire administered before and after students attended anorganic chemistry guest lecture. Data analysis was performed using univariate methods and the chisquare test for statistical analysis. The results of this study showed that the awareness level ofpharmacy students at Muhammadiyah A.R. Fachruddin University, after attending the guest lecture,was at a good level (98%). The p-value <0.001 (<0.05) strongly supports the effectiveness of theguest lecture in enhancing their understanding. The guest lecture ran smoothly, marked by manystudents enthusiastically asking and answering the speaker's questions